Short duration of upper extremity lymphedema correlates with a favorable cytokine response after lymph node transfer surgery - Rannikko Eeva H; Leppäpuska Ida M; Laukka Mervi; Saarikko Anne; Hartiala Pauliina (LYMPHOLOGY, 2022)
Vascularized lymph node transfer surgery (VLNT) can provide benefit to lymphedema patients. Cytokines mayplaya role in the development oflymphedema and in the regeneration oflymphatic vessels after VLNT. Ourprimary aim was to investigate whether the VLNTpatients have a specific cytokine profile. Our secondary aim was to see whether the preoperative lymphedema or severity affects the postoperative cytokine response. Wound exudate was gathered from 18 patients undergoing VLNT on the first and sixth postoperative day (POD). The concentrations of IL-10, TNF-alpha, TGF-beta 1 and VEGF-C were analyzed using enzyme-inked immune-sorbent assays. A general score was generated to assess the benefit ofthe surgery. The changes in cytokine concentrations (1(st) POD-6th POD) were correlated with the pre- andpostoperative lymphedema related factors. A shorter duration oflymphedema preoperatively correlated with an increase in the concentration of IL-10 and TNF-beta during the first six PODs (IL-10: r=0.495, p=0.051; TNF-alpha: p=0.006) and a decrease in the concentration of 7VF-111 (r= p=0.020). The increase ofthe concentration of TNF-alpha during the first six PODs also correlated with a greater total general score (r=0.775, p=0.005) and hence indicated a better response to the surgery. The patients with a shorter duration oflymphedema preoperatively had a more favorable cytokine response during the first six PODs after VLNT.